The Contacts of the Monolayer Semiconductor C2N with 2D Metal Electrodes. Issue 3 (4th January 2019) - Chen, Zhao; Li, Xingxing; Yang, Jinlong
Abstract: For its easy synthesis, suitable band gap, and fine optoelectronic properties, the carbon nitride sheet C2 N acts as a promising candidate material for nanoelectronics. To achieve a high‐performance C2 N device, ohmic contact with metal electrodes is urgently needed. Here, based on first principles calculations, the monolayer (ML) C2 N contacts with a series of 2D metal electrodes—surface‐engineered MXenes (Hf2 C(OH)2, Nb2 CF2, Mo2 NO2 ) and metallic transition metal dichalcogenides ( T ‐VSe2, T ‐VS2, H ‐TaS2 )—are systematically studied. With clean and saturated surfaces, these 2D metals form van der Waals (vdW) contacts with C2 N, which exhibit a weak Fermi level pinning and tunable Schottky barriers. While n‐type Schottky barriers are observed for Nb2 CF2 / T ‐VSe2 electrodes and p‐type for T ‐VS2 /Mo2 NO2 / H ‐TaS2 electrodes due to their different sizes of work functions, ohmic contact is found for Hf2 C(OH)2 electrode with its work function significantly smaller than electron affinity of ML C2 N. Device simulations of field effect transistors based on C2 N further confirmed the finding. This paper presents a fundamental understanding of 2D metal–C2 N contacts and will help the future design of well‐performing C2 N devices. Abstract : The monolayer semiconductor C2 N forms van der Waals contacts with 2D metal electrodes having clean and saturated surfaces, exhibiting a weak Fermi level pinning effect with the Schottky barrier tunable by metal work functions.